Association of side effects to medication adherence of antiepileptic drug use in epileptic patients - Ernawati, Iin; Wyono, Oktaviani Putri; Yunitasari, Fitria Dewi; Pradani, Erwindy Yastika; Islamiyah, Wardah Rahmatul (Faculty of Pharmacy, Universitas Pancasila, 2024)
Epilepsy is a chronic neurological disorder with symptoms characterized by seizures, arising spontaneously with brief episodes with the main symptom of decreased or loss of consciousness. This study aims to examine the effect of side effects of medication adherence to antiepileptic drug use in epilepsy patients. This research is an observational study that was analyzed using quantitative descriptive methods in Neurology patients at the Airlangga University Hospital from March until May 2022. Side effects were measured using the LAEP (Liverpool Adverse Effects Profile) questionnaire and adherence was measured using a pill count. Results showed that the influence of side effects on medication adherence (pill count method) to antiepileptic drugs using linear regression, it is known that the P-value is 0.501. There is no significant relationship between the category of side effects and medication adherence to antiepileptic drugs. Another factor that influences compliance with medication use is the appearance of seizures. Based on the results of this study, it is known that the greater the frequency of seizures, the more likely patients are to be non-compliant (P-value 0.006). To increase adherence, it is necessary to pay attention to other factors such as knowledge, economy, and type of therapy in epilepsy patients so that therapeutic outcomes can be achieved.